ANTIMUTAGENIC EFFECT OF PHENOLIC ACIDS - Birosova, Lucia; Mikulasova, Maria; Vaverkova, Stefania (Biomedical papers, 2005)
In the present study, the Salmonella typhimurium tester strain TA 100 was used in the plate-incorporation test to examine the antimutagenic potential of caffeic, ferulic and cichoric acids extracted from plant species of genera Echinacea (L) Moench, as well as of another phenolic acids, on 3-(5-nitro-2-furyl)acrylic acid (5NFAA) and sodium azide mutagenicity. All tested compounds possess antimutagenic activity. In the case of 5NFAA, the antimutagenic potency of tested compounds was in the order of gallic acid > ferulic acid > caffeic acid > syringic acid > vanillic acid. The mutagenic effect of sodium azide was inhibited by tested phenolic acids by about 20-35 %. The most effective compound, gallic acid inhibits this effect by 82 % in the concentration of 500 μg/plate. The only exception from favourable properties of tested phenolic acids is cichoric acid, which in the contrary significantly increased the mutagenic effect of 5NFAA.
Keywords: Phenolic acid/Antimutagenity/Salmonella typhimurium